THE MECHANISM OF ACTION OF ALLOXAN IN EXPERIMENTAL STUDIES - Sherov Sherzod Abdurasulovich (INTEGRATION OF EDUCATION AND SCIENCE: GLOBAL CHALLENGES AND SOLUTIONS, 2025)
Despite the significant development of diabetology, which is a priority area of health care development in many countries of the world, the problem of prevention, early diagnosis and treatment of diabetes (QD) in children and adults has become an acute medical and social problem. QD, which leads to severe complications and early disability in young organisms, is characterized by high mortality. Cell therapy allows you to ensure the full supply of the body with the necessary peptides and intercellular interaction factors, which contributes to the reparative regeneration of pancreatic tissues, thereby reducing insulin deficiency.